2022
DOI: 10.1002/jcop.22911
|View full text |Cite
|
Sign up to set email alerts
|

Early and continuing grandparental care and middle school students' educational and mental health outcomes in China

Abstract: Several recent studies have examined the relationship between grandparents and grandchildren, but few have examined the effects of early and continuing grandparental care on children's development in China. Using data from the China Education Panel Survey, this study examines the effects of early and continuing care, in which grandparents serve as primary caregivers on middle school students' educational (measured by academic performance and cognitive scores) and mental health (depression score) outcomes. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Children cared for by healthy parents were healthier than those cared for by healthy grandparents. Role conflict and negative sociodemographic factors (such as lower education level and the aging state) may negatively influence the capacity of grandparents to participate in caretaking behaviours and thus impact children's health (Booys et al, 2016; Hong & Zeng, 2022; Joshi & Lebrun‐Harris, 2022). However, good health status enables grandparents to meet children's physiological demands efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children cared for by healthy parents were healthier than those cared for by healthy grandparents. Role conflict and negative sociodemographic factors (such as lower education level and the aging state) may negatively influence the capacity of grandparents to participate in caretaking behaviours and thus impact children's health (Booys et al, 2016; Hong & Zeng, 2022; Joshi & Lebrun‐Harris, 2022). However, good health status enables grandparents to meet children's physiological demands efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of effective communication may further intensify conflicts and their consequences (Hoang et al, 2020). Most studies have found that children raised mainly by grandparents tend to report deteriorating health compared with those cared for by parents (Fan et al, 2010; Hong & Zeng, 2022; Joshi & Lebrun‐Harris, 2022; Liu et al, 2018; Pilkauskas & Dunifon, 2016; Ruiz & Silverstein, 2007; Xu et al, 2022), but exceptions have also been documented (Fruhauf et al, 2022; Pong & Chen, 2010; Tanskanen & Danielsbacka, 2017). For example, a cross‐sectional study conducted in Taiwan reported that children mainly cared for by grandparents achieved higher cognitive scores (Pong & Chen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of focusing on parenting, Hong and Zeng (2022) place a higher value on grandparental care and have examined the effect of early and continuing grandparental care on adolescents' educational and mental health outcomes in contemporary China. They show that grandparental care has been shown to have complex effects on children's outcomes; it varies according to different life stages and by places of residence.…”
Section: Papers In This Special Issuementioning
confidence: 99%
“…For example, the associations between family characteristics and child externalizing problems were more likely to appear in middle school age and onwards (Zeratsion et al, 2015). In terms of living areas, a Chinese study of children receiving grandparental care showed that urban children reported better mental health status than their rural counterparts (Hong & Zeng, 2022). Additionally, regional and cultural contexts are important determinants for grandparental care.…”
Section: Introductionmentioning
confidence: 99%